Acessibilidade como um fator que explica a posse do automóvel: evidências da Região Metropolitana de São Paulo - Schad, Carlos Eduardo (2015)
This study applied the gravity-based accessibility model by public transit and individual modes as an explanatory variable for the number of automobiles in the metropolitan region of São Paulo, using neighborhood level data from the 2007 Metrô Origin and Destination Survey. The regression analysis shows that accessibility by public transit has a negative impact on the number of cars in the city of São Paulo and has no impact on other municipalities in the Metropolitan Region. The conclusion is that a lack of an institution that coordinates public policies for the different municipalities and the São Paulo state prevent significant accessibility improvements